Cautionary Note on Contamination of Reagents Used for Molecular Detection of SARS-CoV-2 - Huggett, Jim F; Benes, Vladimir; Bustin, Stephen A; Garson, Jeremy A; Harris, Karthyn; Kammel, Martin; Kubista, Mikael; McHugh, Timothy D; Moran-Gilad, Jacob; Nolan, Tania; Pfaffl, Michael W; Salit, Marc; et al. (Clinical chemistry (Baltimore, Md.), 2020)
Reverse transcription (RT)-PCR, the principal diagnostic method applied in the world-wide struggle against COVID-19, is capable of detecting a single molecule of a viral genome. Correctly designed and practiced RT-PCR assays for SARS-CoV-2 should not cross react with similar but distinct viral pathogens, such as the coronaviruses associated with the common cold, and should perform with very high analytical sensitivity. This analytical performance is predicated on the ability of the method to detect the presence of the selected nucleic acid target, without detection of a false positive signal.